The Isolation DNA Chromosomal DNA from Local Isolate of Aeromonas hydrophila Bacteria from East Java - Wahjuni, Retno Sri; Yuliani, M. Gandul Atik (Jurnal Vokasi Indonesia, 2018)
Aeromoniasis is a bacterial disease caused by Aeromonas hydrophila that affects fish and shrimps in ponds and aquariums. This is an ulcer disease that causes petechiae in scales of fish and may be fatal. It can cause economic loss if it is not treated with medication accompanied with improved sanitation. It affects numerous freshwater fish farms in East Java. A previous study has characterized an antigenic protein derived from the outer membrane protein of A. hydrophila. In order to perform sequencing of the DNA coding for this protein, we first conducted a study for isolating DNA fragments of A. hydrophila via four stages: cultivation and harvesting of bacterial cells, cell lysis, DNA purification, and the concentration of chromosomal DNA. The results will be used as a predictive immunogenic determinant by the method by Kolaskar and Tongaonkar.